Ministry for Foreign Affairs, Helsinki. Protection of Minority Rights in Finland. Finnish Features. No. 4/65; Aspects of the Language Problem; in Finland. F. F. No. 4/62; Karl Nickul: "The Lapps the people of Lapland". F. F. 33/62; Paavo Ravila: "The Riddle of the Lapps" F. F. 12/61 - U. V, . (Revista Mexicana de Sociología, 1966)
reseña